Somos solteirões: a construção da solteirice na agricultura familiar de Alegrete/RS - Costa, Cassiane da (2014)
This study had as objective to understand bachelordom in family farming of Alegrete, in Rio Grande do Sul State, Brazil. It is a case study with the emphasis on life stories of six bachelor farmers through semi-structured interviews with them and interviews with key informants of the city. Beside the interviews, it was used bibliographical and documental research and observation technique. It was based on the theoretical foundation of the concept célibat paysan , symbolic power, symbolic domination and male domination by Pierre Bourdieu. Bachelordom features very prominently in the rural area of Alegrete, related to masculinisation processes and population ageing. Bachelors from the rural area are concentrated in two social groups: family farmers who work in ranching and cowboys working in farms. Bachelordom phenomenon has been expanding over time favored by the concentration of soldiers army and gauchos (people from Rio Grande do Sul) in that area, the concentration of land tenure, the modernization process and the development of gaucho ideology. As a social field, family provides the basis of affectivity for the bachelors, but is also a space of power play which has been changing over the last decades. There are some characteristics which are shared among the bachelors, as the commitment to family, the positive appreciation of rural life, work and Rio Grande do Sul culture, besides the wish of personal independence. Those similarities provide the emergence of the bachelors‟ identity. Bachelordom is a result of the men‟s decision in keeping single based on several factors as symbolic domination in terms of social and gender classes and ethnicity; family strategies; the condition of masculinisation and rural population ageing; and the positive appreciation of the rural bachelor‟s identity. So, bachelordom in family farming of Alegrete/RS is understood as a social construction.